Accommodation of Vicarious Liability in Advertising Endorsement Agreements in Indonesia - Nuriyyah Nailis Shaadah (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this research is to conduct research on Vicarious Liability accommodations in endorsement agreements. Vicarious Liability is a doctrine in civil law that allows someone to be held legally responsible for the actions of another person, in this case the endorser. Endorsement contract agreements, as a form of compensation between creators and endorsers, have their own characteristics and dynamics that influence the accommodation of the Vicarious Liability doctrine. The current research uses a normative doctrinal research method with a focus on an in-depth analytical approach from various legal standards, such as statutory regulations, court decisions, and legal doctrine relating to the accommodation of vicarious liability in endorsement contract agreements. The analysis was carried out qualitatively by identifying and analyzing arguments and examining the views of relevant legal experts. It is hoped that the results of this research will provide a better understanding of vicarious liability accommodation in endorsement contract agreements, including related legal aspects, controversies and challenges faced in its implementation. It is also hoped that this research can contribute to the development of legal theory and practice in the context of endorsement and vicarious liability agreements in Indonesia.